2017
DOI: 10.4314/ijbcs.v11i4.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation des techniques de production du beurre de karité au Togo

Abstract: RESUMEDe nos jours, la filière karité a une importance socio-économique non négligeable dans le développement des grands producteurs mondiaux de beurre de karité. Le présent travail a pour objectif de faire une enquête sur les profils des unités de production, les procédés de collecte des amandes et de production de beurre, les rendements d'extraction de beurre et les caractéristiques sensorielles des beurres de karité afin de faire l'état des lieux de la filière karité au Togo. Les résultats obtenus ont montr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Hydrolysis and oxidation are consequences of poor oil conservation. Acid number measures the amount of free fatty acids resulting from hydrolytic reactions of triglycerides, making it a quality criterion to report conservation status of an oil (Kpegba et al, 2017). Kandji et al (2001) found an acid number of 2.60 for S. indicum L oil that are close to our values for S. radiatum.…”
Section: Acid Number and Aciditysupporting
confidence: 80%
“…Hydrolysis and oxidation are consequences of poor oil conservation. Acid number measures the amount of free fatty acids resulting from hydrolytic reactions of triglycerides, making it a quality criterion to report conservation status of an oil (Kpegba et al, 2017). Kandji et al (2001) found an acid number of 2.60 for S. indicum L oil that are close to our values for S. radiatum.…”
Section: Acid Number and Aciditysupporting
confidence: 80%
“…It was a species traditionally known in the drier central and northern parts of countries such as Benin, Cameroon, Côte d'Ivoire, Ghana, Nigeria, Togo and Uganda. It was a species of African savannas and more precisely of West Africa where it is known as endemic [65][66][67]. The species was found more in Sudanese and Sudano-Sahelian climates with a rainfall of less than 1000 mm [56].…”
Section: Analysis Of the Dynamics Of Land Cover And Use In The Forest...mentioning
confidence: 99%